2022
DOI: 10.1073/pnas.2119000119
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of free-roaming cat population requires high-intensity neutering in spatial contiguity to mitigate compensatory effects

Abstract: Significance Although popular companion animals, domestic cats pose numerous problems when free-roaming, including predation of wildlife, hazards to humans, impaired sanitation, and a decrease in their welfare. Thus, managing their populations is essential. The trap–neuter–return method (TNR; capturing, sterilizing, returning/releasing) is widely employed for managing cat populations. However, there is a lack of long-term controlled evidence for its effectiveness. We examined the outcomes of high-int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 68 publications
(128 reference statements)
0
35
0
2
Order By: Relevance
“… Feature TE TNR TAR Speed of population reduction Rapid extirpation in closed populations but needs reapplication if abandonment or migration replenishes cats [ 37 , 87 ]. Some local successes are claimed, especially where populations are closed and there is high adoption within the program (e.g., [ 92 , 93 ]); however, Gunther et al [ 60 ] observed that achieving sterilization rates of at least 75% (required for population decline) is ‘almost impossible to reach and sustain on a meta-population scale.’ Gunther et al [ 46 ] reported population reductions of approximately 7% per year following high intensity (>70% neutering) maintained across contiguous sites covering a 20 km 2 urban area. Should be rapid in a closed population because cats are removed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… Feature TE TNR TAR Speed of population reduction Rapid extirpation in closed populations but needs reapplication if abandonment or migration replenishes cats [ 37 , 87 ]. Some local successes are claimed, especially where populations are closed and there is high adoption within the program (e.g., [ 92 , 93 ]); however, Gunther et al [ 60 ] observed that achieving sterilization rates of at least 75% (required for population decline) is ‘almost impossible to reach and sustain on a meta-population scale.’ Gunther et al [ 46 ] reported population reductions of approximately 7% per year following high intensity (>70% neutering) maintained across contiguous sites covering a 20 km 2 urban area. Should be rapid in a closed population because cats are removed.…”
Section: Discussionmentioning
confidence: 99%
“… Should be rapid in a closed population because cats are removed. Needs reapplication when numbers are replenished by migration or abandonment, similar to the problems noted for TE and for TNR that are not applied across contiguous areas simultaneously [ 46 ]. Addresses problems caused by stray cats Yes, if applied at a level that reduces populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it prohibits their elimination, replacing culling (which has successfully eradicated cat populations on certain islands; Nogales et al, 2004) by fertility control (Trap-Neuter-Return/ Release, TNR), which is considered more ethical. However, TNR only enables population reduction when applied at high rates over long time-frames and in spatial contiguity, at very high costs, and with compensatory effects that should be simultaneously managed (Gunther et al, 2022). Such complex, frequently unaffordable management would result in TNR perpetuating or even increasing the already high number of stray cats in cities and rural areas, thus maintaining (in the short-term) and then boosting (over longer time frames) their devastating impacts on biodiversity.…”
mentioning
confidence: 99%